Optimization of Bhabinkamtibmas for the Resolution of Minor Crime Problems through Regional Regulations (Qanun) in the Context of Kamtibmas in the Banda Aceh Police Legal Territory - Zakwan Rifqi (Indonesian Journal of Police Studies, 2021)
Minor Crime (Tipiring) is a case that can be punished with imprisonment for a fixed period of no longer than 3 months and/or a maximum fine of Rp. 7,500 and minor insults, except for traffic offences. In the Criminal Code, Tipiring is regulated in Article 205 Paragraph (1) which is generally applicable, but in Aceh, Tipiring is accommodated in Qanun No. The purpose of this research is to look at the competence of Bhayangkara of Community Security and Order (Bhabinkamtibmas) in solving the Tipiring problem in the jurisdiction of the Banda Aceh Police, including identifying the factors why the Bhabinkamtibmas role is not optimal in the Tipiring problem, next is to find out what is the problem. efforts and methods of Bhabinkamtibmas in dealing with the Tipiring problem. This study uses a descriptive qualitative research method, which examines and examines referring to the phenomena and facts that occur in the field. The responsibility of the National Police is a very noble task and has a very broad authority, especially in solving problems. Based on the results of the study, there were several obstacles and obstacles such as bhabin being picked up at the SPK, the lack of activity from bhabin so that coordination with stakeholders did not go well even many people did not know who Bhabinkamtibmas was in their village. So that the researcher uses the theory of Synopsis Planning and the theory of Competence in answering the problems in this study. Bhabinkamtibmas is the spearhead of the police force that is closest to the community, so it is necessary to take action in optimizing competencies such as holding bhabinkamtibmas education and training and the application of rewards so that bhabinkamtibmas can be competent in solving tipiring problems that will affect the state budget for the investigative function, which can save billions of rupiah in national funds. The realization of kamtibmas and being able to work well with stakeholders in the village and be liked by the community.